Therapeutic Ultrasound in Cardiovascular Medicine. (21st September 2020) - Coiado, Olivia C.; Lowe, Jacques; O'Brien, William D.
Abstract : An advantage of therapeutic ultrasound (US) is the ability to cause controlled biological effects noninvasively. Depending on the magnitude and frequency of exposure parameters, US can interact in different ways with a variety of biological tissues. The development and clinical utility of therapeutic US techniques are now rapidly growing, especially with regard to the application of US pulses for cardiac pacing and the potential treatment of cardiovascular diseases. This review outlines the basic principles of US‐based therapy in cardiology, including the acoustic properties of the cardiovascular tissue, and the use of US in therapeutic cardiovascular medicine.